Proceedings of the 19th SIGBioMed Workshop on Biomedical Language Processing 2020
DOI: 10.18653/v1/2020.bionlp-1.17
|View full text |Cite
|
Sign up to set email alerts
|

Domain Adaptation and Instance Selection for Disease Syndrome Classification over Veterinary Clinical Notes

Abstract: Identifying the reasons for antibiotic administration in veterinary records is a critical component of understanding antimicrobial usage patterns. This informs antimicrobial stewardship programs designed to fight antimicrobial resistance, a major health crisis affecting both humans and animals in which veterinarians have an important role to play. We propose a document classification approach to determine the reason for administration of a given drug, with particular focus on domain adaptation from one drug to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Increased use of bacterial cultures and susceptibility testing is likely to improve the clinical outcomes while reducing the importance ratings of the antimicrobials used. While there were labels with culture and sensitivity annotated in the original corpus used to train the disease syndrome classifier, 17 , 47 there were not enough of these labels to train the model. Evaluation of the antimicrobial susceptibility of isolates obtained from canine urine cultures in Australia demonstrated that antimicrobial agents of lower critical importance could be selected without compromising efficacy, 48 but further work is required to incorporate clinical pathology data into VetCompass and evaluate this in a large scale dataset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased use of bacterial cultures and susceptibility testing is likely to improve the clinical outcomes while reducing the importance ratings of the antimicrobials used. While there were labels with culture and sensitivity annotated in the original corpus used to train the disease syndrome classifier, 17 , 47 there were not enough of these labels to train the model. Evaluation of the antimicrobial susceptibility of isolates obtained from canine urine cultures in Australia demonstrated that antimicrobial agents of lower critical importance could be selected without compromising efficacy, 48 but further work is required to incorporate clinical pathology data into VetCompass and evaluate this in a large scale dataset.…”
Section: Discussionmentioning
confidence: 99%
“…A model referred to as VetBERT was used to classify the indication for disease. 17 VetBERT was created using a model known as ClinicalBERT 28 as a base and then using additional pretraining steps as described by Devlin et al . 24 using the entire corpus of 15 million clinical notes from VetCompass Australia to provide a good representation of the veterinary clinical text.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al (2019) used BERT for domain-discriminative data selection. Hur et al (2020) used BERT for domain adaptation and instance selection for disease classification. Our selection method is similar to these methods but focuses on selecting conversational-style sentences.…”
Section: Related Workmentioning
confidence: 99%